Pengaruh Identitas Diri dan Dukungan Sosial Keluarga terhadap Quarter Life Crisis Pada Mahasiswa - Khafidza, Zahwa; Andjarsari, Fara Dwi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Quarter life crisis is an emotional crisis experienced by individuals during their transition period to show theirself-existence and responsibility in completing various tasks and challenges, which gives rise to strong negativefeelings of worry about the future life. This research aims to determine the influence of self-identity and familysocial support on the quarter life crisis in 2020 Faculty of Economics students at Djuanda University, Bogor. Thisresearch uses quantitative methods. The population in this study amounted to 178 samples with a total of 122respondents using the quota sampling technique. The results of the research analysis show that there is asignificant influence in the positive direction between self-identity and the quarter life crisis with an R value of0.504, R2 of 0.254 and Bx1y of 1.063 with p (0.001) < 0.05. Meanwhile, there is a significant influence in thenegative direction between family social support on the quarter life crisis R with an R value of 0.299, R2 of 0.089and Bx1y of -0.482 with p (0.001) < 0.05. The results of data analysis using Multiple Linear Regression usingSPSS 29.0 for Windows obtained an R value of 0.517, R2 of 0.268 and Bx1y of 0.201 with p (0.001) < 0.05.